Chemical Composition and Anti-Microbial Activity of Hog Plum (Spondias mombin L.) Peel Oil Extracted from Different Regions of Tropical Climates - Md. Emrul Ahsan Plabon (MDPI AG, 2021)
The hydro-distilled essential oil of hog plum peel may be used for enhancing the flavor and taste of food products as well as for hiding the unpleasant odor of drugs. Thus, the waste peels of Spondias mombin appear to have economic importance. To find out the chemical composition and anti-microbial properties of hog plum peel oil, the samples were collected from different regions of Bangladesh for extraction and identification of volatile compounds by GC-MS, where dichloromethane was used as an extraction solvent. The required standard analytical methods were used to assay the anti-microbial properties of hog plums. In this study, pentenyl-3-thy-met-4-alpha-methyl-alpha-ethanol-oxiranen (29.04%), (3,3.1,1)-4-dimethylethyl-1,1-phenol (8.00%), cycohexanol-3 (10.85%), 4-hydroxy-penzeneethanamine (7.09%), hydroxylamine (4.63%), dibutyl phthalate (6.85%), etc., were majorly determined. Consequently, the highest content of 75.81% volatile compounds was found in the Dinajpur district, where the lowest content of 35.00% was found in the Rajshahi district. In contrast, 33 volatile compounds were identified in hog plum peels collected from the Barishal district, whereas 22 compounds were detected in the peel samples collected from the Dinajpur district. In addition, the antimicrobial activity of the oil was analyzed by the disk diffusion method, and the results revealed that the highest Ciprocin content was recorded in the hog plums of Barishal (22.0–23.0 mm), while the lowest was recorded in the Mymensingh sample (20.67–21.63 mm), which was on par with Rajshahi sample (20.70–21.50 mm). The results of the anti-fungal activities of the peel oil showed the highest zone of inhibition against the Aspergillus niger (11.63 ± 0.0003 mm) and Penicillium oxalicum (13.67 ± 1.97 mm) content of the Rajshahi and Pabna district samples, respectively.